Instability of the Eurozone? On monetary policy, house prices and labor market reforms - Ansgar Belke; Daniel Gros (Institute for the Study of Labor (IZA), 2007)
This paper deals with potential instabilities in the Eurozone stemming from an insufficient interplay between monetary policy and reform effort on the one hand and the emergence of intra-Euro area divergences on the other. As a first step, we assess the effect of EMU on structural reform and investigate this question by an examination of the relationship between fixed exchange rates and reform in two wider samples of countries. We also stress that loose monetary conditions, which prevailed until some months ago, can also manifest themselves in asset price inflation, notably in the housing market. When these bubbles burst (e.g., when housing prices stop rising) this often leads to a prolonged period of economic instability and weakness rather than consumer price inflation. As a second step, we point out that risks for EMU are not only increasing because longer-term disequilibria become evident in fiscal and monetary policy, but also because serious divergences are now appearing within the Euro area which threaten its long-term cohesiveness. The most manifest example of this threat comes from what promises to be a long-term divergence between Germany and Italy, which for the time being was offset by asynchronous developments of house prices in both countries. There are still large differences within the Euro area, with the small countries performing much better than the large ones on almost every indicator. This suggests that better policies can make a large difference even if monetary policy is the same for everybody
urn:nbn:de:101:1-20080425493
Keywords: 330; Europäische Wirtschafts- und Währungsunion; Wirtschaftsreform; Wirtschaftliche Anpassung; Immobilienpreis; Regionale Preisstruktur; Wirtschaftliche Instabilität; Geldpolitik; Theorie; EU-Staaten